LOS SUPLEMENTEROS: LOS NIÑOS Y LA VENTA DE DIARIOS. CHILE, 1880-1953 - Rojas, Jorge (Ariadna Ediciones, 2006)
Historical reconstruction of the role of children selling newspapers in the 19th and 20th centuries in Chile